Understanding Pupil Violence: Bullying Theory as Technoscience in Sweden and Norway - Boge, Cecilie; Larsson, Anna (Nordic Journal of Educational History, 2018)
Around 1970, violence among pupils became conceptualised in a radically new way when the concept of “mobbing” was introduced into the Nordic school debate. The concept was immediately embraced by popular discourse with the result that significant attention and discussion followed. It was also soon picked up by researchers and became further developed within Swedish and Norwegian behavioural science. This article concerns how pupil violence in the form of bullying was understood and theorised in the 1970s, 1980s and 1990s in Sweden and Norway. It shows how certain political and intellectual conditions, and events, in both national contexts were decisive for the development of bullying theory, eventually leading up to a commercialisation of bullying theory. This development is discussed with the help of the concept “psychology-commercial complex,” derived from Pickstone’s theory of technoscience.